"PAY IT FORWARD" AND HIGHER EDUCATION SUBSIDIES: A MEDIAN VOTER MODEL. (6th March 2017) - Delaney, Jennifer A.; Dharmapala, Dhammika
Abstract : Since 2012, at least 24 states have considered legislation on Pay It Forward (PIF) models of higher education finance (which enable students to pay the price of college upon departure from an institution, as opposed to paying upfront tuition). This paper proposes a theoretical model of PIF policies within a framework in which voters belonging to different income groups vote over the level of subsidies to higher education. We analyze the impact of two types of potential PIF policies—a deferred tuition approach and an income share approach—on college access and on voting equilibria over subsidy levels. The results show that college access is enhanced by PIF policies. The equilibrium level of subsidies depends crucially on the pattern of income distribution, in particular on the relationship between mean income and the income of the median income group, and on whether higher education widens or narrows the distribution of income. We show that the equilibrium level of subsidies to higher education will not necessarily decline under PIF, and may increase in some circumstances due to changes in college access for low‐income groups. ( JEL I22, I23)